PENGARUH ASPEK SARANA PRASARANA DAN MINAT BELAJAR SISWA TERHADAP HASIL BELAJAR SISWA SMK NEGERI SARANA PRASARANA DAN MINAT BELAJAR SISWA TERHADAP HASIL BELAJAR SISWA SMK NEGERI : THE INFLUENCE OF ASPECTS OF FACILITIES AND STUDENTS' LEARNING INTEREST ON STUDENTS' LEARNING OUTCOMES STATE VOCATIONAL SCHOOL - yunita (Universitas Sarjanawiyata Tamansiswa, 2024)
The purpose of this research is to determine: (1) the level of infrastructure aspects, (2) the level of learning interest, (3) learning outcomes, (4) the influence of infrastructure aspects on learning outcomes, (5) the influence of learning interest on learning outcomes, (6) the simultaneous influence of infrastructure aspects and learning interest on learning outcomes. The analysis techniques involve descriptive analysis and hypothesis testing using prerequisite analysis tests. The research findings indicate that (1) the infrastructure aspect is in the moderate category, (2) learning interest is in the moderate category, (3) learning outcomes are in the high category, (4) there is a positive influence of in infrastructure aspects on learning outcomes, (5) there is a negative influence of learning interest on learning outcomes, and (6) there is a significant negative influence of learning interest on learning outcomes.